Swahili: A Donor Language - Baldi, Sergio (Lingua Posnaniensis, 2011)
Swahili is a Bantu language, more specifically a member of the Sabaki subgroup of North East Coast Bantu. Swahili was first written in Arabic script, in which there are manuscripts dating back to the early 18th century. A Roman alphabet which is now standard was introduced during the colonial period, although some Swahili-speaking Muslims continue to use Arabic script, especially in private correspondence. The cultural importance of Islam is reflected in the large number of loanwords from Arabic. Swahili is the national language in Tanzania and Kenya and largely spoken in the nearby countries. It has also an important role as a donor language in East Africa and Central Africa, not only to other Bantu idioms, but also to other languages belonging to different linguistic families.